RESPON PERTUMBUHAN DAN PRODUKSI SAWI (Brassica sinensis L.) DENGAN PEMBERIAN MINERAL ZEOLIT DAN NITROGEN - Bram Arda Bintario Bangun; Jasmani Ginting; Ferry Ezra Sitepu (Jurnal Agroekoteknologi, 2014)
Production Growth response and mustard (Brassica sinensis L,.) By Giving Mineral Zeoliteand Nitrogen, guided by Jasmani Ginting dan Ferry Ezra Sitepu. This study aims to test theresponse of the growth and production of mustard on the provision of zeolite and ureafertilizer. The study was conducted in community land Setia Budi Road Simpang SelayangMedan district in May to July 2012. Experimental method used was a factorial randomizedblock design with 2 factors, namely the provision of zeolite (0 g, 50 g / plot, 100 g / plot, 150g / plot) and urea fertilizer (without urea, 0.2 g / tan. , 0.4 g / tan., 0.6 g / plant) with 3replications. The parameters measured were plant height, leaf area, leaf chlorophyll amount,weight biomass per plant, fresh weight per plant and sell the sample harvest index. The resultsshowed that administration of zeolite significant effect on all parameters. While the treatmentof urea fertilizer and the interaction between the two treatments did not significantly affect allparameters.Keywords: zeolite, urea, growth and production of mustard.